2016
DOI: 10.1117/1.jbo.21.8.087007
|View full text |Cite
|
Sign up to set email alerts
|

Detection and capture of breast cancer cells with photoacoustic flow cytometry

Abstract: Abstract. According to the Centers for Disease Control and Prevention, breast cancer is the most common cancer and the second leading cause of cancer related deaths among women. Metastasis-the presence of secondary tumors caused by the spread of cancer cells via the circulatory or lymphatic systems-significantly worsens the prognosis of any breast cancer patient. A technique is developed to detect circulating breast cancer cells in human blood using a photoacoustic flow cytometry method. A Q-switched laser is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…PAFC combines traditional flow cytometry with PA detection to characterize CTCs in flow . Several studies have demonstrated the value of PAFC for its ability to isolate and identify specific cells using either endogenous or exogenous chromophores to generate contrast. , PAFC has several advantages over traditional flow cytometry including its ability to specifically identify cells of interest deep in human tissues and its ease of translation to in vivo applications . These PAFC systems show great promise; however, to the best of the authors’ knowledge, no study has yet utilized PAFC for the detection of ovarian CTCs.…”
Section: Resultsmentioning
confidence: 99%
“…PAFC combines traditional flow cytometry with PA detection to characterize CTCs in flow . Several studies have demonstrated the value of PAFC for its ability to isolate and identify specific cells using either endogenous or exogenous chromophores to generate contrast. , PAFC has several advantages over traditional flow cytometry including its ability to specifically identify cells of interest deep in human tissues and its ease of translation to in vivo applications . These PAFC systems show great promise; however, to the best of the authors’ knowledge, no study has yet utilized PAFC for the detection of ovarian CTCs.…”
Section: Resultsmentioning
confidence: 99%
“…Based on photoacoustic effect Bhattacharyya et al [60] used photoacoustic flow cytometry (PAFC) to detect CTCs in the peripheral blood of patients with breast cancer. It works by the absorption of laser light through nanoparticles labeled with antibodies on target cells.…”
Section: Based On Inertiamentioning
confidence: 99%
“…It works by the absorption of laser light through nanoparticles labeled with antibodies on target cells. They also found that this method could be used to study the response of patients with breast cancer to treatment as well as in vitro drug trials [ 60 ].…”
Section: Isolation Based On Physical Propertiesmentioning
confidence: 99%
“…When cell sensing is performed in diagnosis, a sensitivity of at least 10-45 cells/ mL is required [10,11]. In order to count cells in the clinical setting, a cell counter [12], hemocytometer [13], and a flow site meter are used [14,15]. Although these methods are practical, clinical systems in the field require low-cost apparatus introduction, superior sensitivity, and simple steps.…”
Section: Introductionmentioning
confidence: 99%